Analisis Faktor-Faktor yang Berpengaruh terhadap Ibu Hamil Trimester III Melakukan Antenatal Care K4 - Lia Fitria (Politeknik Negeri Jember, 2018)
Antenatal Care (ANC) is one of the supporting factors to reduce maternal mortality. The maternal mortality rate in Indonesia reaches 228 / 100,000 and the target to be achieved in the Millennium Development Goals (MDGs), which is equal to 110 per 100,000 live births. This study aims to analyze the factors associated with the low coverage of Antenatal Care K4. The research design in this study is a survey. The population in this study were all Trimester III pregnant women in Sumberejo Village by using purposive sampling. The data that has been obtained is analyzed using multiple logistic regression tests. Data that has been obtained from the assessment was analyzed using multiple logistic regression statistical tests. In the knowledge factor, the value of p = 0.541, while the distance factor for pregnant women to health workers is p = 0.019. Based on the results of the above analysis, it can be concluded that the knowledge factor Ho is accepted, meaning that there is no influence of knowledge factors on third trimester pregnant women doing Antenatal Care K4, while the distance factor for pregnant women Ho is rejected, meaning that there are influences of perception factors and distance of pregnant women to health workers against Antenatal Care K4. It is hoped that the results of this study can be useful especially for health workers to improve Antenatal Care K4 as a means of early detection of a complication of pregnancy or childbirth.